2022
DOI: 10.1091/mbc.e22-01-0018
|View full text |Cite
|
Sign up to set email alerts
|

Tau differentially regulates the transport of early endosomes and lysosomes

Abstract: Microtubule-associated proteins (MAPs) modulate the motility of kinesin and dynein along microtubules to control the transport of vesicles and organelles. The neuronal MAP tau inhibits kinesin-dependent transport. Phosphorylation of tau at tyrosine 18 by fyn kinase results in weakened inhibition of kinesin-1. We examined the motility of early endosomes and lysosomes in cells expressing wild-type (WT) tau and phosphomimetic Y18E tau. We quantified the effects on motility as a function of the tau expression leve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…1 D–F). This difference might be the result of a phosphorylated form of tau that inhibits kinesin-3 function, but not kinesin-1, even more strongly than the non-phosphorylated form ( Balabanian et al, 202 2). By inhibiting kinesin motors, tau favors retrograde endosomal movement ( Chaudhary et al, 2018 ).…”
Section: Motor Proteins Bind Microtubule Tracks To Transport Endosomesmentioning
confidence: 99%
“…1 D–F). This difference might be the result of a phosphorylated form of tau that inhibits kinesin-3 function, but not kinesin-1, even more strongly than the non-phosphorylated form ( Balabanian et al, 202 2). By inhibiting kinesin motors, tau favors retrograde endosomal movement ( Chaudhary et al, 2018 ).…”
Section: Motor Proteins Bind Microtubule Tracks To Transport Endosomesmentioning
confidence: 99%
“…Several studies have shown that tau is a general inhibitor of motor transport, reducing the landing rate for all transport motors: kinesin‐1, kinesin‐2, kinesin‐3, and the processive dynein‐dynactin complex (Balabanian et al, 2022; Chaudhary et al, 2018; Dixit et al, 2008; Ebneth et al, 1998; Monroy et al, 2018; Monroy et al, 2020; Tan et al, 2019; Figure 1a). The effects on kinesin motors are more pronounced than on the dynein motor, due in part to the overlapping binding sites of tau and kinesin motor domains on the microtubule lattice (Tan et al, 2019).…”
Section: The Role Of Tau Envelopes: Competition With Maps Motors and ...mentioning
confidence: 99%
“…16 It regulates the MTs assembly and spatial organization, 17 and controls the motility of motor proteins on MTs. [18][19][20][21] Tau is involved in numerous neurodegenerative diseases, named tauopathies, including Alzheimer's disease (AD), which are characterized by fibrillar aggregation. 22 The binding of tau on MTs, and its propensity to aggregate are affected by PTMs, in particular the hyperphosphorylation of tau has been shown to be involved in several pathologies.…”
Section: Introductionmentioning
confidence: 99%